Genetic Characterization of Domesticated F1 Generation in Humpback Grouper (Cromileptes altivelis) - Ratu Siti Aliah; . Wahidah; K. Sumantadinata; Estu Nugroho; O. Carman (Jurnal Akuakultur Indonesia)
First generation (F1) of hatchery produced humpback grouper (Cromileptes altivelis) has been characterized genetically in order to serve the information of their status in related to their breeding strategy. PCR-RFLP method was used to detect the variation of mtDNA D-loop region of F1 population at BBPBL Lampung and BBAP Situbondo. The result of study showed that reducing of haplotype diversity had been arised from broodstock (0.8548) to F1 generation population (0.7473; 0.7273; and 0.6947, respectively).  Genetic divergence that had found between population BBPBL Lampung and BBAP Situbondo make it possible to do outbreeding in order to get its heterosis's effect.